Measurement of joint health in persons with haemophilia: A systematic review of the measurement properties of haemophilia‐specific instruments - Gouw, Samantha C. (Haemophilia, 2018)
INTRODUCTION: Accurate assessment of joint health in persons with haemophilia is crucial. Several haemophilia‐specific measurement tools are available, but an overview of the measurement properties is lacking. AIM: To provide an overview of the measurement properties of haemophilia‐specific measurement tools to assess clinical joint health. METHODS: MEDLINE and EMBASE were searched for reports on reliability, validity or responsiveness of the World Federation of Haemophilia Orthopedic Joint Score (WFH), Colorado Physical Examination Score (CPE), joint examination score by Petrini (PJS) and Hemophilia Joint Health Score (HJHS). Methodological quality of the studies was assessed using an adapted COSMIN checklist. RESULTS: The search yielded 2905 unique hits, and 98 papers were included. The methodological quality of the included studies was limited. The HJHS was studied most extensively, which yielded limited evidence for good internal consistency and structural validity, moderate evidence for hypothesis testing in adults and conflicting evidence for hypothesis testing in children. Reliability, measurement error and responsiveness were rated unknown due to low COSMIN scores. For the CPE and PJS, we found limited to moderate evidence for good responsiveness and conflicting evidence for hypothesis testing. CONCLUSION: Only patchy evidence is available on the quality of measurement properties of all haemophilia‐specific joint health scores. Although significant gaps in the evidence for all instruments remain, measurement properties of the HJHS were most extensively studied and show no drawbacks for use in clinical practice. This review forms the basis for further research aimed at the assessment of measurement properties of measurement tools to assess joint health.